2005
DOI: 10.1007/s10493-004-5082-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of azadirachtin on the two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae)

Abstract: Effects of sublethal azadirachtin exposure to the biological performance of Tetranychius urticae Koch was studied under laboratory conditions. Bioassay was used to asses the effect of different concentrations of azadirachtin on longevity, fecundity, fertility, and offspring development. Azadirachtin (64 and 128 ppm) affected fecundity and mortality but had no effect on fertility and offspring development. A subsequent life-table study with 80 ppm of azadirachtin found that the compound caused a reduction of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 22 publications
0
22
1
1
Order By: Relevance
“…For neem based products, this approach is especially important due to their special mode of action and delayed effects on arthropods (Scmutterer 1990). Besides direct mortality (Momen et al 1997, Castiglioni et al 2002, neem causes reduction in fertility (Dimetry et al 1993), longevity and fecundity of mites (Martínez-Villar et al 2005). Thus, subletal effects should be considered when selecting neem concentrations for mite control.…”
Section: July -August 2010mentioning
confidence: 99%
“…For neem based products, this approach is especially important due to their special mode of action and delayed effects on arthropods (Scmutterer 1990). Besides direct mortality (Momen et al 1997, Castiglioni et al 2002, neem causes reduction in fertility (Dimetry et al 1993), longevity and fecundity of mites (Martínez-Villar et al 2005). Thus, subletal effects should be considered when selecting neem concentrations for mite control.…”
Section: July -August 2010mentioning
confidence: 99%
“…Dentre as plantas como fontes de inseticidas naturais, o nim (Azadirachta indica A. Juss) tem se destacado pela sua eficiência por afetar negativamente a biologia e o comportamento de pragas, apresentar baixa toxicidade para vertebrados, além da seletividade a diversos inimigos naturais (CASTAGNOLI et al, 2002;MOURÃO et al, 2004;MARTINEZ-VILLAR et al, 2005).…”
Section: Introductionunclassified
“…M.: Mortality C.: Concentrations. Also, it was observed that the extracts showed reduced fecundity on the female of T. urticae [31,32]. Pure azadiractin reduced the number of eggs laid by T. urticae [33].…”
Section: Effect On Egg Laying Capacitymentioning
confidence: 99%